Predation scars provide a new method to distinguish native and invasive crab predation on mollusc prey - Kristina M. Barclay; Paige Amos; Lindsey R. Leighton; Chris L. Schneider; Julia K. Baum (Ecology and Evolution, 2024)
Abstract Crab species are increasingly important socioeconomic resources that are threatened by human exploitation, climate change, and invasive species, such as European green crabs (Carcinus maenas). However, the continued health of their populations is often uncertain given the limited long‐term population data, necessitating alternate approaches to ensure their continued viability. Furthermore, C. maenas are one of the most highly invasive and destructive marine species globally, posing a threat to local ecosystems and species, including socioeconomically important crabs and their mollusc prey. Improved understanding of C. maenas invasions and their impacts on local crab and mollusc resources is therefore vitally important. Here, we present a new method for identifying species‐level presence and relative abundances of important crab species, including invasive C. maenas, from the scars they leave on their prey. We conducted controlled manipulative feeding experiments in which individuals of Dungeness crabs (Metacarcinus magister), red rock crabs (Cancer productus), and C. maenas, were allowed to attack snails (Tegula funebralis) and produce sublethal shell damage. Resulting shell damage was photographed and landmarked for geometric morphometric analyses to determine any differences in the shape of shell damage between crab species. There were statistically significant differences between the shape of shell damage created by all three crab species (p < .0001). Shell damage formed a gradient from narrow/deep (C. productus) to shallow/wide (C. maenas) with M. magister as an intermediate form. Our method provides a novel, cost‐effective tool for long‐term species‐specific reconstructions of crab populations and assessing the broader ecological impacts of C. maenas invasions that can inform management and mitigation for these three important crab species.